Tinjauan Hukum Terhadap Investasi Syariah Berbasis Mudharabah dan Musyarakah di Pasar Modal Indonesia - Mulyadi, Salsabila; Saskia Br Sitepu, Drep Salna (Journal Of Law And Social Society, 2025)
In the Indonesian business world, sharia investment is growing rapidly in line with public demand. One of the efforts being made is to develop the economy in the capital market sector. In the development of sharia capital market instruments, mudharabah and musyarakah contracts play a very important role, as they form the basis for the publication of various investment products such as funding sukuk, capital cooperation instruments, and others. The purpose of this study is to examine the application of sharia investment with mudharabah and musyarakah contracts in the capital market in Indonesia and to analyze the legal challenges in the application of sharia investment based on mudharabah and musyarakah contracts in the Indonesian capital market. This study uses a normative legal research method, namely by reviewing relevant legal literature. The results of this study indicate that the application of sharia investment is carried out with mudharabah and musyarakah contracts in capital market transactions in Indonesia and must be in accordance with sharia principles. However, in practice, there are still several challenges, such as investors' limited understanding of sharia contracts in capital market transactions and the need for more comprehensive investment supervision. Therefore, efforts are needed to overcome these challenges, such as improving regulations governing sharia investment, strengthening the function of the Sharia Supervisory Board, and increasing literacy about sharia finance so that investments based on mudharabah and musyarakah contracts can develop in accordance with the principles of Islamic law. Keywords: Sharia Investment, Mudharabah, Musyarakah, Capital Market